2011
DOI: 10.1051/0004-6361/201116663
|View full text |Cite
|
Sign up to set email alerts
|

The extinction curves of star-forming regions fromz = 0.1 to 6.7 using GRB afterglow spectroscopy

Abstract: Studies of extinction curves provide insights into the properties of interstellar dust. Until recently, however, very few extinction curves existed outside the local group. GRB afterglows are well suited to extinction studies due to their brightness, simple power-law spectra and their occurrence in distant star forming galaxies. In this paper we present results from the SED analysis of a sample of 41 GRB afterglows, from X-ray to NIR wavelengths. The sample is based on spectra from VLT-FORS, with additional da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
198
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(218 citation statements)
references
References 166 publications
17
198
3
Order By: Relevance
“…This indicates that for at least 10-15% of the extinguished GRBs in our sample, the host galaxy extinction curve has a 2175 Å feature. This is in good agreement with the results from Zafar et al (2011), who studied the extinction curve for a sample of 41 GRB afterglows using combined, broadband Fig. 2.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This indicates that for at least 10-15% of the extinguished GRBs in our sample, the host galaxy extinction curve has a 2175 Å feature. This is in good agreement with the results from Zafar et al (2011), who studied the extinction curve for a sample of 41 GRB afterglows using combined, broadband Fig. 2.…”
Section: Resultssupporting
confidence: 91%
“…In the latter case the spectral break was modelled as the cooling frequency, ν c , such that the change in slope, δβ, was fixed at 0.5 (Sari et al 1998), and the spectral break was constrained to lie within the UV to X-ray energy range. The physical plausibility of such a change in spectral index is also supported by the analysis of Zafar et al (2011), who did not constrain the spectral slopes in their SED analysis, but found Δβ to be typically ∼0.5. We considered a broken power-law model to provide a better fit to the afterglow spectral continuum when the F-test returned a null hypothesis probability smaller than 5%.…”
Section: Sed Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…The location of the flux-drop is in the rest-frame ultraviolet and it is therefore natural to explore whether this can be an extreme example of the 2175 Å extinction bump known from the Milky Way and also previously seen in GRB afterglow spectra (Ellison et al 2006;Fynbo et al 2007;Krühler et al 2008;Elíasdóttir et al 2009;Prochaska et al 2009;Zafar et al 2011). This feature is ubiquitous in the MW and in M 31.…”
Section: A Giant 2175-å Extinction Bumpmentioning
confidence: 92%
“…Those objects are typically relatively high mass, evolved systems. Zafar et al (2011) showed in an analysis of GRB afterglows that GRB host galaxies, which are typically young and star-forming with low metallicities and hard radiation environments (Christensen et al 2004;Castro Cerón et al 2006;Savaglio et al 2009;Svensson et al 2010;Chary et al 2002;Fynbo et al 2008;Watson et al 2010), have substantially lower dust-to-gas ratios than the local group even after accounting for metallicity.…”
Section: Extragalactic Metals-to-dust Ratiosmentioning
confidence: 99%